2019
DOI: 10.1002/wrna.1538
|View full text |Cite
|
Sign up to set email alerts
|

Intriguing circles: Conflicts and controversies in circular RNA research

Abstract: Circular RNAs (circRNAs) are covalently closed RNA circles without a 5 0 cap or 3 0 tail. Since the landmark discovery of ciRS-7/CDR1as functioning as a miR-7 sponge in 2013, circRNAs have become a hot topic in RNA research. CircRNAs have been found to play active roles in cancer, cardiovascular diseases, neurological disorders, and many other diseases. They can function as microRNA (miRNA) sponges, protein scaffolds, and even translation templates. However, as circRNA research expands, many divergent views ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
99
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(102 citation statements)
references
References 129 publications
(398 reference statements)
1
99
0
2
Order By: Relevance
“…circRNA is characterized by the covalently closed loop structure without 5′‐end cup and 3′‐end ploy‐A tail. It is widely expressed in eukaryotic cells and possesses important gene regulatory potential, which makes it involved in tumorigenesis and aggressiveness . Recent studies have shown that circRNA functions through different actions, including serving as ‘miRNA sponge’, regulation of transcription and splicing, interacting with RNA‐binding protein, and even translating polypeptide .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…circRNA is characterized by the covalently closed loop structure without 5′‐end cup and 3′‐end ploy‐A tail. It is widely expressed in eukaryotic cells and possesses important gene regulatory potential, which makes it involved in tumorigenesis and aggressiveness . Recent studies have shown that circRNA functions through different actions, including serving as ‘miRNA sponge’, regulation of transcription and splicing, interacting with RNA‐binding protein, and even translating polypeptide .…”
Section: Discussionmentioning
confidence: 99%
“…It is widely expressed in eukaryotic cells and possesses important gene regulatory potential, which makes it involved in tumorigenesis and aggressiveness. 15 Recent studies have shown that circRNA functions through different actions, including serving as 'miRNA sponge', regulation of transcription and splicing, interacting with RNA-binding protein, and even translating polypeptide. 16 The most extensively studied is circRNA as a competing endogenous RNA (ceRNA) to effectively sponge miRNA, for example, circ-HIPK3/miR-7 in colorectal cancer, 17 circ-EPSTI1/miR-942 in ovarian cancer, 18 circ-ANKS1B/ miR-148/152 in breast cancer 19 and circ-AMOTL1L/miR-193a-5p in prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
“…CircRNA, a class of enclosed non-coding RNA molecules generated by RNA splicing, function as an miRNA sponge and regulate gene transcription and alternative splicing. 4,5,8,13,18,19 Recent studies have confirmed that circRNA is involved in the regulation of gene expression by various means, thereby indirectly participating in the occurrence and development of various solid cancers. 6,[9][10][11]13,14,16,17 However, the biological functions of circRNA in BC are scarcely reported.…”
Section: Discussionmentioning
confidence: 99%
“…CircRNA, a class of enclosed non-coding RNA molecules generated by RNA splicing, function as an miRNA sponge and regulate gene transcription and alternative splicing [18,19,8,13,4,5]. Recent studies have confirmed that circRNA is involved in the regulation of gene expression by various means, thereby indirectly participating in the occurrence and development of various solid cancers [13,11,10,6,17,9,16,14].…”
Section: Discussionmentioning
confidence: 99%